1996
DOI: 10.1088/0953-2048/9/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Melting of the flux line lattice

Abstract: Since the recent discovery of the high-temperature superconductors, there have been many ideas put forward to explain the phase diagram. One of the most important parts of this phase diagram is the so called irreversible line. The majority opinion is that this line represents a phase transition from a flux line solid to a flux line fluid, that is a melting transition. The following is a brief review of some of the ideas put forward to explain this. † In the case of low magnetic field the irreversible line and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Such drastic features are associated with a first order phase transition for the lattice vortex melting. 10,11 These results are consistent with computer simulations in the three-dimensional ͑3D͒ XY model [12][13][14][15][16] and others. 17 The first-order-like transition seems to remain even in the presence of some ͑simulated through the XY exchange integral͒ static disorder 14͑b͒ but not in the presence of point defects ͑introduced by irradiation͒.…”
supporting
confidence: 90%
“…Such drastic features are associated with a first order phase transition for the lattice vortex melting. 10,11 These results are consistent with computer simulations in the three-dimensional ͑3D͒ XY model [12][13][14][15][16] and others. 17 The first-order-like transition seems to remain even in the presence of some ͑simulated through the XY exchange integral͒ static disorder 14͑b͒ but not in the presence of point defects ͑introduced by irradiation͒.…”
supporting
confidence: 90%
“…In general, the Jc(H) curves have a field decrease that prevents determining the irreversibility field Hirr (evaluated as Jc ≈ 100 A/cm 2 ) even for the highest temperature shown in Figure 3 (11 K) and at 9 T. In order to deeply study the Jc(H) anomalous behavior reported in Figure 3, the Jc curves as a function of temperature Jc(T) at different fields were extracted from the Jc(H). In particular, by fitting the Jc(T) behavior with several pinning models reported in the literature [51][52][53][54][55][56][57], it is possible to determine the pinning regime acting in the sample. Among the pinning models, the three equations that best fit our experimental data across the field range are the following ones: In order to deeply study the J c (H) anomalous behavior reported in Figure 3, the J c curves as a function of temperature J c (T) at different fields were extracted from the J c (H).…”
Section: Resultsmentioning
confidence: 99%
“…Similar dependencies have been introduced to account for the existence of the "giant flux creep" [60][61] , taking the pinning potential as U p = H c 2 (t) * (a 0 2 ξ), where a 0 2 = φ 0 B is the area of a unit cell of the flux lines lattice 59) . The macroscopic force F p results also in this case from a direct summation procedure of elementary pinning forces, f p =U p /λ, where λ is the London penetration depth.…”
Section: -The Non-linear Diffusion Equationmentioning
confidence: 99%